Clinical case of a pelvic fracture with massive retroperitoneal hematoma - Krishtafor , D.A.; Krishtafor, A.A.; Tsarev, A.V.; Balyk , D.V.; Halushchak , A.Y.; Pelekh, V.A. (Medicni Perspektivi, 2023)
Pelvic fracture is a serious injury that carries a significant risk of mortality. The cause of death in these victims is the formation of a retroperitoneal hematoma and massive bleeding. The article presents a clinical case of a pelvic fracture with a massive retroperitoneal hematoma in a 30-year-old man who was brought to the regional hospital in hemorrhagic shock 5 hours after falling from the 5th floor. Upon admission, computed tomography (CT) showed a rupture of the pubic joint, a multifragmentary fracture of the sacrum, and the presence of a hematoma in the right parts of the pelvic cavity. Despite immobilization of the fracture and massive transfusion, it was not possible to stabilize the patient’s hemodynamics and improve the parameters of the patient’s general blood analysis. Due to the clinic of active bleeding, the patient repeatedly underwent control ultrasound examinations of the abdominal cavity and pleural sinuses, but the presence of free fluid in the abdominal cavity could be confirmed only after 12 hours of treatment. At the emergency laparotomy, a hematoma was found, which spread through the retroperitoneal space to the level of the diaphragmatic crura and the root of the small-bowel mesentery in a relatively thin layer, which explained the impossibility of its visualization by ultrasound or CT. Despite the intensive care measures, over the next few days the patient’s condition gradually worsened, multiple organ failure developed. On the 3rd day after the operation, the patient died due to progressive multiple organ failure. The described case demonstrates the severity of the condition of victims with a traumatic retroperitoneal hematoma and the difficulty of diagnosis and effective treatment using conservative methods.